MIND MAPPING SEBAGAI STRATEGI DALAM PEMBELAJARAN BERBICARA (SPEAKING) - Ririn Pusparini, ; Esti Kurniasih, (Widya Cendika, 2011)
This research is descriptive research that aims to get a description of the effectiveness of Mind Mapping strategy in speaking teaching and learning process. The subject of the research is students of the educational program of UNESA English Department 2009 A, and they are 24 students. The setting of the research is in English Department campus of UNESA. It is in Lidah Wetan. The data sources are material documents, lesson plan document, observation result, and the field notes.From the data analysis result, it is known that the application of Mind Mapping strategy in speaking teaching learning process run well. It was proven by the students capability in constructing Mind Mapping related to the article given by the lecturer. Beside that, students were also able to present an article with free topic. By applying Mind Mapping strategy, students were able to present a topic clearly and in good arrangement.